Joint Effect of Childhood Abuse and Family History of Major Depressive Disorder on Rates of PTSD in People with Personality Disorders. (3rd April 2012) - Flory, Janine D.; Yehuda, Rachel; Passarelli, Vincent; Siever, Larry J.
Abstract : Objective . Childhood maltreatment and familial psychopathology both lead to an increased risk of the development of posttraumatic stress disorder (PTSD) in adulthood. While family history of psychopathology has traditionally been viewed as a proxy for genetic predisposition, such pathology can also contribute to a stress-laden environment for the child. Method . Analyses were conducted to evaluate the joint effect of childhood abuse and a family history of major depressive disorder (MDD) on diagnoses of PTSD and MDD in a sample of 225 adults with DSM-IV Axis II disorders. Results. Results showed that the rate of PTSD in the presence of both childhood abuse and MDD family history was almost six-fold (O R = 5.89,     P = .001 ) higher relative to the absence of both factors. In contrast, the rate of MDD in the presence of both factors was associated with a nearly three-fold risk relative to the reference group (O R = 2.75,     P = .01 ). Conclusions . The results from this observational study contribute to a growing understanding of predisposing factors for the development of PTSD and suggest that joint effects of family history of MDD and childhood abuse on PTSD are greater than either factor alone.